Esophageal Inlet Patch. (27th February 2011) - Behrens, C.; Yen, Peggy P. W.
Abstract : An inlet patch is a congenital anomaly consisting of ectopic gastric mucosa at or just distal to the upper esophageal sphincter. Most inlet patches are largely asymptomatic, but in problematic cases complications related to acid secretion such as esophagitis, ulcer, web and stricture may occur. The diagnosis of inlet patch is strongly suggested on barium swallow where the most common pattern consists of two small indentations on the wall of the esophagus. The diagnosis of inlet patch is confirmed via endoscopy with biopsy. At endoscopy, the lesion appears salmon-coloured and velvety and is easily distinguished from the normal grey-white squamous epithelium of the esophagus. The prominent margins correlate with the radiological findings of indentations and rim-like shadows on barium swallow. Histopathology provides the definitive diagnosis by demonstrating gastric mucosa adjacent to normal esophageal mucosa. No treatment is required for asymptomatic inlet patches. Symptomatic cases are treated with proton pump inhibitors to relieve symptoms related to acid secretion. Strictures and webs are treated with serial dilatation and should be biopsied to rule out malignancy.